The disappearing tax base: is foreign direct investment eroding corporate income taxes? - Reint E. Gropp; Kristina Kostial (European Central Bank (ECB), 2000)
This paper analyzes the link between Foreign Direct Investment (FDI), corporate taxation, and corporate tax revenues. We find strong evidence that FDI in (out) flows are affected by tax regimes in the host (home) countries and FDI flows in turn affect the corporate tax base. Simulations of EU harmonization (isolating the revenue effect of FDI on the tax base from direct effects through the rate harmonization) suggest that high (low) tax countries would gain (lose) revenue from harmonization; these effects may be substantial. Our results also suggest that EU tax harmonization would significantly affect the net FDI position of some countries.
Keywords: H25; H87; F21; F42; F47; 330; corporate taxation; Foreign Direct Investment; OECD countries; revenues; simulations